Analysis of Procedure Implementation Performance Audit by Yaniswar Public Accounting Office and Makassar Branch Partners - Nurfadilla; Samsinar; S, Masnawaty (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
The aim of this study For analyze How Application Performance Audit Procedures carried out by the Public Accounting Firm Yaniswar Dan Rekan Makassar Branch (Case Study of Performance Audit at RSUD Prof. Dr. HM Anwar Makkatutu Regency Bantaeng ). The variable that becomes the focus of this research is application performance audit procedures carried out by the Yaniswar Dan Rekan Branch Public Accounting Firm with use studies Performance Audit case at RSUD Prof. Dr. HM Anwar Makkatutu Regency Bantaeng. Population in this research is an auditor. Retrieval technique sample used is purposive sampling so that obtained sample as many as 1 resource person that is chairman team. Data collection techniques use observation, interviews, and documentation. Data analysis techniques using analysis descriptive qualitative. Based on results study application performance audit procedures by the Public Accounting Firm Yaniswar and Rekan Makassar Branch began from stage audit planning , stage implementation of audits and stages audit reporting. Yaniswar Public Accounting Firm and Partners Makassar Branch implemented performance audit procedures based on Regulation Director General Treasury Number Per-36/PB/2016 used as guidelines in evaluate performance of the Sector Public Service Agency Health services.